The Politics of Asylum: Evaluating Non-Refoulement and Protection Systems for At-Risk Populations - Azzahra, Aisha (Sinergi International Journal of Law, 2025)
This study explores the complex dynamics surrounding the implementation of non-refoulement and the protection of vulnerable refugee groups. The objective is to synthesize normative and empirical findings to examine systemic challenges and identify strategies for improvement. Using a narrative review approach, the study analyzes multidisciplinary literature across legal, political, and humanitarian domains to uncover patterns in refugee policy and practice. The review finds that despite widespread recognition of non-refoulement as a fundamental principle, implementation gaps persist due to bureaucratic inefficiencies, national security-driven policies, and political rhetoric. Vulnerable groups—such as women, children, and LGBTQ+ individuals—face systemic discrimination and reduced access to justice and social services. Comparative international analysis highlights disparities in protection standards between developed and developing nations, particularly in legal capacity and resource deployment. Solutions proposed in the literature include adopting intersectional approaches, establishing transparent asylum procedures, enhancing institutional coordination, and deploying digital systems to monitor claim evaluations. The study concludes that policy reform must prioritize inclusive frameworks grounded in human rights, with tailored protections for marginalized populations. Further research is needed to assess the impact of these strategies and address implementation constraints. These insights are critical to building responsive and equitable refugee protection systems that uphold international legal standards.